2020
DOI: 10.1155/2020/6915483
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Response inPseudomonas aeruginosatowards Treatment with a Kaempferol Isolated fromMelastoma malabathricumLinn Leaves

Abstract: Pseudomonas aeruginosa is one of the main causes of nosocomial infections and is frequently associated with opportunistic infections among hospitalized patients. Kaempferol-3-O-(2′,6′-di-O-trans-p-coumaroyl)-β-D glucopyranoside (KF) is an antipseudomonal compound isolated from the leaves of the native medicinal plant Melastoma malabathricum. Herein, an RNA-seq transcriptomic approach was employed to study the effect of KF treatment on P. aeruginosa and to elucidate the molecular mechanisms underlying the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Kaempferol could decrease the expression of genes involved in biofilm formation in P. aeruginosa . The type IV and flagellin type B (fliC) genes’ downregulation in response to kaempferol observed in RNA-seq was paralleled by the decreased expression of genes which are involved in biofilm formation in P. aeruginosa [ 33 ]. Rutin, which is also found in Citrus maxima , showed a concentration-dependent reduction of biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Kaempferol could decrease the expression of genes involved in biofilm formation in P. aeruginosa . The type IV and flagellin type B (fliC) genes’ downregulation in response to kaempferol observed in RNA-seq was paralleled by the decreased expression of genes which are involved in biofilm formation in P. aeruginosa [ 33 ]. Rutin, which is also found in Citrus maxima , showed a concentration-dependent reduction of biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when counting the number of lung colony in the coinfection mice model, it was found that both kaempferol treatment and prevention group could reduce the number of P. aeruginosa in lung tissue, indicating that kaempferol could effectively inhibit the growth of P. aeruginosa in vivo and in vitro. Mourouge et al found that Kaempferol-3o-(2 ,6 -di-o-trans-p-coumaryl)-β-d-glucopyranoside (KF) isolated from Melastomataceae, which can inhibit P. aeruginosa by inhibiting the expression of virulence factors, affects its nutrient absorption, movement, and growth mechanism when they studied the use of plants to treat acute P. aeruginosa infections, indicating that kaempferol has great potential in the inhibition of P. aeruginosa [38].…”
Section: Discussionmentioning
confidence: 99%